How Iranian women conceptualize mental health: an explanatory model. - Arash Mirabzadeh; Ameneh Setareh Forouzan; Farahnaz Mohammadi; Masoumeh Dejman; Monir Baradaran Eftekhari (Tehran University of Medical Sciences, 2014)
In Iran, more than 25% of women suffer from mental disorders. Mental disorders and subclinical problems are associated with socioeconomic problem. At the community level, mental health promotion can reduce social damage. The aim of this study as a part of community based mental health promotion intervention was to explore how mental health in Iranian women is viewed.According to a qualitative method in 2012, participants were selected by purposeful sampling from married women 18 to 65 years who are residents in Tehran. Fifteen in depth individual interviews were conducted with regard to the concept of mental health, causal pathway and help-seeking behavior according to explanatory model.Mental health was perceived as the same of emotional well-being. It conceptualized not only lack of mental disorder but also sense of satisfaction and healthy functioning. According to participant's view, the causal pathway of mental health problems were classified to individual, familial and social factors. Physical and behavioral problems were related to individual factor, Lack of marital adjustment was one of the most important issues in familial item and in social factor, cultural context and socio-economic problems were extracted. In help seeking process, all of the participants believed that the religion has important effect in mental health.Marital adjustment is an important stage in process of mental health in women.